1985
DOI: 10.1118/1.595691
|View full text |Cite
|
Sign up to set email alerts
|

Lung dose corrections for 6‐ and 15‐MV x rays

Abstract: We have measured the radiation dose in simple heterogeneous phantoms and compared our results with those obtained by various methods of computation. Dose data were obtained both within and distal to simulated regions of lung in order to test the ratio of tissue-air ratios (TAR), Batho, and equivalent TAR methods. These procedures are used routinely in manual and computer-aided planning of radiation therapy, but have been validated primarily for cobalt-60 radiation. Tests performed with 6- and 15-MV x rays reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
65
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 0 publications
11
65
0
1
Order By: Relevance
“…The essential volume over which scatter of kernel contributions must be necessitated and the maximum volume used in XiO planning system is close to 30cm in the forward direction, 5cm in the backward direction, and replicate the field size dimension laterally (basically the contributions from all interaction points must be collected). Sharpe and Battista 11 have reported the same ranges, as well as Mackie et al 12,13 have described the same As well as dose contributions above such a large area needs a significant time for computation. This computation time can be reduced by accomplishment separate calculations; one with the main core for which the computation is done at a high resolution, but over a small region, the other with a scatter kernel where a computation is achieved at a lower resolution but over a large area, as suggested by Mackie et al 5,8 .…”
Section: Convolution Algorithmsupporting
confidence: 52%
“…The essential volume over which scatter of kernel contributions must be necessitated and the maximum volume used in XiO planning system is close to 30cm in the forward direction, 5cm in the backward direction, and replicate the field size dimension laterally (basically the contributions from all interaction points must be collected). Sharpe and Battista 11 have reported the same ranges, as well as Mackie et al 12,13 have described the same As well as dose contributions above such a large area needs a significant time for computation. This computation time can be reduced by accomplishment separate calculations; one with the main core for which the computation is done at a high resolution, but over a small region, the other with a scatter kernel where a computation is achieved at a lower resolution but over a large area, as suggested by Mackie et al 5,8 .…”
Section: Convolution Algorithmsupporting
confidence: 52%
“…Studies involving accuracy of treatment planning software with respect to inhomogeneous phantoms have been the subject of many publications 1,4,5,7,[10][11][12][13]15,20 . These studies show significant discrepancies between measured and calculated dose near interfaces between tissues of different density.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have shown the existence of significant dose perturbation within, and beyond, low‐density inhomogeneities for small fields of megavoltage photons 4 7 . The perturbations in lung result from the combined effects of a reduction in photon attenuation, loss of scattered photons, and increase in range of the secondary electrons.…”
Section: Introductionmentioning
confidence: 99%